2021
DOI: 10.31235/osf.io/46mnb
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Systematizing Confidence in Open Research and Evidence (SCORE)

Abstract: Assessing the credibility of research claims is a central, continuous, and laborious part of the scientific process. Credibility assessment strategies range from expert judgment to aggregating existing evidence to systematic replication efforts. Such assessments can require substantial time and effort. Research progress could be accelerated if there were rapid, scalable, accurate credibility indicators to guide attention and resource allocation for further assessment. The SCORE program is creating and validati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 48 publications
0
26
0
Order By: Relevance
“…We employ the following heuristics to identify this data: We sample 100 PubMed sentences from Yu et al (2019) that are identified as having low causal content. We sample 50 titles from SBS paper present in Alipourfard et al (2021), as titles contain factors but rarely contain explicit associations and may be present in input data from automatically extracted text from PDFs. Finally we sample 50 first lines of SBS papers from Alipourfard et al (2021), as these lines frequently introduce topics or rhetorical questions which either lack associations or present highly hypothetical associations unlike those in our main corpus.…”
Section: Discussionmentioning
confidence: 99%
“…We employ the following heuristics to identify this data: We sample 100 PubMed sentences from Yu et al (2019) that are identified as having low causal content. We sample 50 titles from SBS paper present in Alipourfard et al (2021), as titles contain factors but rarely contain explicit associations and may be present in input data from automatically extracted text from PDFs. Finally we sample 50 first lines of SBS papers from Alipourfard et al (2021), as these lines frequently introduce topics or rhetorical questions which either lack associations or present highly hypothetical associations unlike those in our main corpus.…”
Section: Discussionmentioning
confidence: 99%
“…We employ the following heuristics to identify this data: We sample 50 PubMed sentences from Yu et al (2019) that are identified as having low causal content. We sample 100 titles from SBS paper present in Alipourfard et al (2021), as titles contain factors but rarely contain explicit associations and may be present in input data from automatically extracted text from PDFs. Finally we sample 50 first lines of SBS papers from Alipourfard et al (2021), as these lines frequently introduce topics or rhetorical questions which either lack associations or present highly hypothetical associations unlike those in our main corpus.…”
Section: Discussionmentioning
confidence: 99%
“…To extend relational scientific information extraction to specifically target scientific claims, we annotate SciClaim, 1 a dataset of 12,738 annotations on 901 sentences from expert identified claims in Social and Behavior Science (SBS) papers (Alipourfard et al, 2021), detected causal language in PubMed papers (Yu et al, 2019), and claims and causal language heuristically identified from CORD-19 abstracts (Wang et al, 2020).…”
Section: Levels Of Social Supportmentioning
confidence: 99%
See 1 more Smart Citation
“…The SciClaim scientific claim schema is designed to capture associations between factors (e.g., causation, comparison, prediction, proportionality), monotonicity constraints across factors, epistemic status, and high-level qualifiers. This model is used for qualitative reasoning to help characterize the replicability and reproducibility of scientific claims (Alipourfard et al, 2021;Gelman et al, 2021). We describe the entities, attributes, and relations of the schema, referencing the graphed examples rendered by our system in Figures 1, 2, and 3.…”
Section: Knowledge Graph Schemasmentioning
confidence: 99%